Role of Fur on cyanide tolerance of Pseudomonas pseudoalcaligenes CECT5344. (21st November 2011) - Becerra, Gracia; Blasco, Rafael; Quesada, Alberto; Merchán, Faustino; Igeño, M. Isabel
Abstract : Pseudomonas pseudoalcaligenes CECT5344 can be used in cyanide bioremediation processes because it grows at pH 9.5 using 2.0 mM cyanide at the sole nitrogen source. Cyanide strongly binds to metals creating iron-deprivation conditions. The bacterium responds to the presence of cyanide by inducing several processes such as siderophore synthesis for iron capture, cyanide-insensitive respiration system and defence mechanisms against oxidative stress. Since high concentrations of cyanide cause iron deficiency and because iron is an essential nutrient, bacterial growth in the presence of cyanide requires an efficient iron uptake. Fur is a global transcription factor that regulates a diversity of biological processes such as iron homoeostasis, TCA (tricarboxylic acid) cycle metabolism and oxidative stress response. Fur's regulation of iron uptake and storage genes should play a significant role in the lives of these bacteria. In the present review, current knowledge of Fur is summarized.